FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN INFRASTRUKTUR - Machmuddah, Zaky; Ali, Shujahat; Abiyyatha, Muhammad Kafa (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2025)
The aim of this study was to investigate the elements influencing firm values empirically. Infrastructure companies with listings on the IDX constitute the population. The sample used in this research includes companies listed on the Indonesian Stock Exchange. 166 observation data points were gathered over a four-year period, or the 2020–2023 timeframe. The SPSS version 26 software program is the use of multiple linear regression in an analytical process. The outcomes of the analysis of the study show that return on equity (ROE) or total asset turnover (TATO) has an impact on a company's worth. In the meanwhile, the value of the business is unaffected by the current ratio (CR) and debt-to-equity ratio (DER). When making investment selections, investors should consider DER, CR, ROE, and TATO, according to the research's implications.